Particularities of methodology of investigation of passenger cars arsons - Pasovets Владимир Николаевич; Kovtun Вадим Анатольевич; Goroshko Елена Юрьевна; Tagiev Шамхал Шахин (Journal of Civil Protection, 2022)
Purpose. Improvement the methodology for investigating fires on motor vehicles. Methods. Theoretical analysis, synthesis, systematization. Findings. The article is devoted to the investigation of cases of fires in cars. The stages of inspection of vehicles during arson are described taking into account modern trends in the development of forensic tactics, particularities of working with physical evidence, means, techniques and methods for detecting and removing traces. Application field of research. The presented results can be used in law enforcement activities in the investigation of fires on vehicles.